Values of Lithuanian managers - Bajoriūnienė, J. (Psichologija, 1996)
This work deals with the work-related values of Lithuanian managers. As values depend upon many different factors, we decided to find out which of these are the most important. According to G. Hofstede, the director of the Intercultural Collaboration Research Institute, national culture is especially important in understanding the success of management. E. H. Schein indicates organizational culture as no less important. This work hereby describes the work-related values of Lithuanian managers (indicated with Hofstede's Values Survey) and confirms Hofstede's conclusion that national culture has a stronger influence on values formation than organizational culture.
Keywords: values; orgalizational culture; managers